Commentary on “Does Ultrasonography Contribute Significantly to the Diagnosis of Carpal Tunnel Syndrome?” by A. Zyluk, I. Walaszek and Z. Szlosser - Kamolz, L. P.; Kitzinger, H. B. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2014)
The diagnosis of carpal tunnel syndrome diagnosis can be made based on the history and clinical findings in most of the cases, but in doubtful cases, electrophysiological tests and ultrasound can provide additonal and useful information.
Keywords: N. medianus; carpal tunnel syndrome; decompression